2019
DOI: 10.1016/j.redox.2019.101214
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol enrichment in liver mitochondria impairs oxidative phosphorylation and disrupts the assembly of respiratory supercomplexes

Abstract: Mitochondrial cholesterol accumulation is a hallmark of alcoholic and non-alcoholic fatty liver diseases and impairs the function of specific solute carriers through changes in membrane physical properties. However, its impact on mitochondrial respiration and organization of respiratory supercomplexes has not been determined so far. Here we fed mice a cholesterol-enriched diet (HC) supplemented with sodium cholate to examine the effect of cholesterol in mitochondrial function. HC feeding increased liver choles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
79
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(80 citation statements)
references
References 48 publications
1
79
0
Order By: Relevance
“…Accumulation of cholesterol in the mitochondria membrane has been shown to impair the activity of some membrane proteins such as the 2‐oxoglutarate carrier that exports 2‐oxoglutarate in the cytosol in exchange of the import of GSH in the mitochondria. Moreover, it has been shown that the accumulation of mitochondrial cholesterol can damage the respiratory chain complexes assembly (Solsona‐Vilarrasa et al, 2019). Under GSH depletion, the cells potentially tried to stabilize the mitochondria membrane and favorize GSH import in the mitochondria matrix by lowering cholesterol.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulation of cholesterol in the mitochondria membrane has been shown to impair the activity of some membrane proteins such as the 2‐oxoglutarate carrier that exports 2‐oxoglutarate in the cytosol in exchange of the import of GSH in the mitochondria. Moreover, it has been shown that the accumulation of mitochondrial cholesterol can damage the respiratory chain complexes assembly (Solsona‐Vilarrasa et al, 2019). Under GSH depletion, the cells potentially tried to stabilize the mitochondria membrane and favorize GSH import in the mitochondria matrix by lowering cholesterol.…”
Section: Discussionmentioning
confidence: 99%
“…Similar changes were demonstrated in diabetic mice that were fed with a high cholesterol diet. In these animals, the rate of mitochondrial state 3 respiration, the value of the mitochondrial membrane potential, and the assembly of the respiratory supercomplexes in mitochondria of the liver were reduced [ 111 ]. Some studies also revealed that a diabetes-induced decline in the activity of complexes of the respiratory chain can be associated with a decreased content or altered composition (peroxidation) of cardiolipin, a main anionic phospholipid in the inner mitochondrial membrane (see review [ 54 ]).…”
Section: Mechanisms Of the Diabetes-induced Mitochondrial Dysfunctmentioning
confidence: 99%
“…Perhaps significantly, increased contacts between mitochondria and endosomes, and correspondingly decreased contacts between ER and endosomes, have recently been reported in NPC1‐deficient cells (Höglinger et al ). However, this idea is also problematic as mechanisms for cholesterol‐induced mitochondrial toxicity have been postulated (Torres et al ; Solsona‐Vilarrasa et al ) but not yet proved and an alternate explanation has recently been offered (Yambire et al ). Additionally mitochondria play a role in cellular cholesterol homeostasis for they house Cyp27A1 an enzyme responsible for converting cholesterol to 27‐hydroxycholesterol, a ligand of the liver X receptor (LXR).…”
Section: Npc1mentioning
confidence: 99%